HUBUNGAN TINGKAT STRES DENGAN PERILAKU MEROKOK PADA SISWA KELAS XII JURUSAN OTOMOTIF DI SMK IBNU SINA KOTA BATAM - Rini Susanti; Rusdani (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Stress must happen to anyone and anywhere, stress affects a person's health condition, especially on changes or behavioral deviations, one of which is smoking behavior. One of the people who are prone to smoking behavior is students. This study aims to determine the relationship between stress levels and smoking behavior in class XII students in automotive affairs at Ibnu Sina Vocational School, Batam City. This research is an analytic observational study with a cross sectional approach. This research was conducted at the Ibnu Sina Vocational School in Batam City from 17 December 2020 to 20 December 2020. The population in this study was 90 class XII students majoring in automotive. So the number of samples in this study amounted to 73 people. To determine the relationship between stress levels and smoking behavior in class XII students of automotive affairs at Ibnu Sina Vocational School, the data analysis used was Spearman's Rank. The relationship between stress level and smoking behavior in class XII students in automotive affairs at Ibnu Sina Vocational School (p=0.001).Based on the results of this study, it can be concluded that there is a significant relationship between stress levels and smoking behavior in class XII students of the Automotive Department at Ibnu Sina Vocational School with a p value of 0.001 (p < 0.05) with a correlation coefficient of 0.393.